Effects of stimulation frequency, amplitude, and impulse width on muscle fatigue. Issue 4 (29th December 2015) - Behringer, Michael; Grützner, Sebastian; Montag, Johannes; McCourt, Molly; Ring, Matthias; Mester, Joachim
ABSTRACT: Introduction : We investigated the effect of stimulation intensity (in percent of maximal tolerated stimulation current, mTSC), frequency, and impulse width on muscle fatigue. Methods : Using a randomized crossover design, 6 parameter combinations (80% mTSC, 80 Hz, 400 μs; 60% mTSC, 80 Hz, 400 μs; 80% mTSC, 20 Hz, 400 μs; 60% mTSC, 20 Hz, 400 μs; 80% mTSC, 80 Hz, 150 μs; 60% mTSC, 80 Hz, 150 μs) were tested in both legs of 13 athletic men (age 26 ± 2.3). The slope of the linear regression line over all tetani (FIS) and the number of tetani whose force was above 50% of the initial tetanus (FIN) were used to quantify fatigue. Results : FIS and FIN were significantly lower in high‐frequency protocols. No effects on FIS and FIN were found for intensity and impulse width. Conclusions : Stimulation frequency, but not impulse width or intensity, affected fatigue kinetics. Muscle Nerve 53 : 608–616, 2016